Biofriendly substitutes for xylene in deparaffinization - Viswanathan Prema; Harikrishnan Prasad; Kenniyan Kumar Srichinthu; Singaravelu Suresh Kumar; Krishnan Rajkumar; Chinnannan Marudhamani (Wolters Kluwer Medknow Publications, 2020)
Background: Xylene is an aromatic hydrocarbon that is routinely used in histopathological laboratories. It is biohazardous and produces many toxic effects like carcinogenesis. A safer substitute for xylene is necessary to minimize its usage. Aim: The aim of this study was to evaluate the effectiveness of 1.7% dishwashing solution, 95% lemon water, and 100% coconut oil when compared to xylene as a deparaffinizing agent during hematoxylin and eosin (H&E) staining. Materials and Methods: Fifteen paraffin-embedded tissue blocks were selected. Four sections were made from each block. One section was stained with conventional H&E method using xylene (group A) as deparaffinizing agent and other three sections were stained with xylene-free H&E method using 1.7% dishwashing solution (group B), 95% lemon water (group C), and 100% coconut oil (group D), respectively. Slides were scored blindly by a single pathologist considering the parameters such as nuclear and cytoplasmic staining; uniformity, clarity, and crispness of staining; and presence or absence of wax retention. Results: Adequate nuclear staining was noted in 100% of sections of groups A, B, C, and D (P < 0.001), whereas adequate cytoplasmic staining was noted in 93.33% each in groups A, C, and D when compared with 100% in group B (P > 0.05). Uniform staining was present in 80% of groups A and B and in 73.33% of groups C and D (P > 0.05). Clarity of staining was present in 86.66% of groups A and B and in 80% of groups C and D (P > 0.05), whereas crispness of staining was seen in 73.33% of groups A and D, 86.66% of group B, and 80% of group C (P > 0.05). Wax retention was noted in 20% of groups A and B, and 26.66% of groups C and D (P > 0.05). Adequate staining for diagnosis was noted in 100% of group A sections followed by 93.33% in group B, 86.66% in group C, and 80% in group D as compared with 90% in group B (P > 0.05). Conclusion: Dishwashing solution, lemon water, and coconut oil can be used as safer and cost-effective substitutes to xylene for deparaffinization in H&E staining procedure.